Biaxial strength determination of woven fabric composite for airship structural envelope based on novel specimens. (15th January 2018) - Shi, Taibai; Chen, Wujun; Gao, Chengjun; Hu, Jianhui; Zhao, Bing; Wang, Ping'an; Wang, Mei
Abstract: Since the high altitude airship provides an economical platform for earth observation, telecommunication and space exploration, its structural envelope materials attracted wide research interests. Although the uniaxial strength was studied extensively, it cannot properly characterize the real strength of the envelope due to the normal biaxial tensile state in operation service. The biaxial strength determination, which is the key parameter related to the airship structural strength, remained unsolved due to the stress concentration and unsatisfactory failure location. This paper presents a new specimen design and test method for biaxial strength ascertaining. A high-speed camera was employed to capture the biaxial failure process of specimens. According to photographs, single slit or crossed slits failure may occur when materials reached their load bearing limits. The authentic biaxial failure stress was obtained utilizing numerical software. Other than the previous perspective, the biaxial strength equals the lower uniaxial strength multiplied by an amplification factor of 1.1–1.3 under a 1:1 stress ratio. The further work may focus on expanding the test range with various load ratios, which could complete a precise failure envelope in biaxial plane stress space.